Live-Ticker: zu der neuen multimodal-hypertextuellen Form der Live-Berichterstattung - Smułczyński, Michał (Folia Scandinavica Posnaniensia, 2020)
The live broadcast of different, socially important events is nowadays no longer reserved only for radio and television. The live-ticker, a result of various media convergence processes, is a multimodal and interactive set of institutional reports, journalists’ and politicians’ opinions, pictures, short films and social media posts, that 24/7 provides the most up-to-date information on a specific topic. The article is an investigation into the media genre live-ticker with a focus on its multimodal structure, the language-image relations, as well as aspects of hypertextuality. Finally, I want to show what the live ticker differs from similar forms of online broadcasting. The corpus are three Danish live-tickers that provided the most detailed report on the trial of the Danish entrepreneur and designer Peter Madsen: bt.dk, ekstrabladet.dk and jyllands-posten.dk. Madsen murdered in 2017 a Swedish journalist Kim Wall, for which he was sentenced in April 2018 to life imprisonment.